Hepatitis B and C viruses and survival from hepatocellular carcinoma in the Arkhangelsk region: a Russian registry-based study - Makarova, Maria; Krettek, Alexandra; Valkov, Mikhail Y.; Grjibovski, Andrej (International Journal of Circumpolar Health, 2013)
Introduction. Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. The prevalence of hepatitis B (HBV) and C (HCV) in Russia was 7.6 and 5.4 per 100,000, respectively. The aim of this study was to assess the proportion of HCV and HBV infection among HCC patients, to evaluate associations between HCV, HBV and stage of HCC and to compare survival of HCC patients by their HBV/HCV status in the Arkhangelsk region of northwest Russia. Materials and methods. A retrospective cohort study was conducted using data on all histologically confirmed HCC cases. Proportions of infected and non-infected HCC cases were calculated by Wilson's method. The associations between HBV, HCV and severity of HCC were assessed by Pearson's Chi-squared test. Survival data were presented using Kaplan–Meier curves and median survival. Survival time between the groups was compared using log-rank tests. Adjustment for potential confounders (sex, age groups, stage of HCC and cirrhosis stage by Child-Paquet scale) was performed using Cox regression. Results. There were 583 histologically confirmed HCC cases. The viral status was registered in 311 of patients with pre-mortem diagnosis, where 124 or 39.9% (95% confidence interval (CI), 34.4–45.4) had HBV, 54 or 17.4% (95% CI, 13.5–21.9) had HCV and 16 or 5.1% (95% CI, 3.2–8.2) were infected with both HBV and HCV. The median survival rates of patients were 3 months (95% CI, 2.3–3.8), 3 months (95% CI, 2.0–3.9) and 1 month (95% CI, 0.0–0.6) for patients with HBV, HCV and HBV and HCV, respectively. For virus-free patients, it was 5 months (95% CI, 3.5–6.5), log-rank test=10.74, df=3, p=0.013. Crude Cox regression showed increased risk of death for HBV and HBV and HCV groups in comparison with virus-free patients, and not reaching the level of statistical significance for HCV. After adjustment, the hazard ratios (HRs) decreased to non-significant levels or even reversed, with only exception for the group of patients infected with both hepatitis viruses. Conclusions. We found that ...